A methodological approach for assessing cross-site landscape change: Understanding socio-ecological systems - Sunderland, Terry C.H.; Abdoulaye, R.; Ahammad, R.; Asaha, S.; Baudron, Frédéric; Deakin, E.L.; Duriaux Chavarria, J.Y.; Eddy, I.; Foli, S.; Gumbo, D.J.; Khatun, K.; Kondwani, M.; et al. (Elsevier, 2017)
The expansion of agriculture has resulted in large-scale habitat loss, the fragmentation of forests, significant losses in biological diversity and negative impacts on many ecosystem services. In this paper, we highlight the Agrarian Change Project, a multi-disciplinary research initiative, that applies detailed socio-ecological methodologies in multi-functional landscapes, and assess the subsequent implications for conservation, livelihoods and food security. Specifically, the research focuses on land use impacts in locations which exhibit various combinations of agricultural modification/change across a forest transition gradient in six tropical landscapes, in Zambia, Burkina Faso, Cameroon, Ethiopia, Indonesia and Bangladesh. These methods include integrated assessments of the perceptions of ecosystem service provision, tree cover loss and gain, relative poverty, diets and agricultural patterns of change. Although numerous surveys on rural livelihoods are undertaken each year, often at great cost, many are hampered by weaknesses in methods and thus may not reflect rural realities. We attempt to highlight how integrating broader socio-ecological methods can be used to fill in those gaps and ensure such realities are indeed captured. Early findings suggest that the transition from a forested landscape to a more agrarian dominated system does not necessarily result in better livelihood outcomes and there may be unintended consequences of forest and tree cover removal. These include the loss of access to grazing land, loss of dietary diversity and the loss of ecosystem services/forest products.